Fotografia, cidade e candomblé: a lavagem do Bonfim de Marcel Gautherot - Aratanha, Emilia Jorge de (2017)
The presente work aims to discuss the views that the french photographer Marcel Gautherot (radicated in Brazil since 1939) has of the festivities of the Lavagem do Bonfim, in a series of fotos taken around 1955. Gautherot, who developed his carrier due to his passion for traveling, permits us to see a different portrayal of the Brazilian Candomblé due to his status as a foreigner. With his almost ethnographic point of view, Gautherot sheds light into another side of this African-brazilian religion: that of the usage of public space in a period in time that black people had severe restrictions on movement and use of public space. Other contemporary photographers set their lenses towards recording what was inside the private space of the Terreiro, while Gautherot sees the Candomblé practitioners in public, utilizing the city